A biomechanical method to improve individual planning and controlling of training - Tilp, M.; Sust, M.; Thaller, S. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
A biomechanical method is shown which helps to determine the most important performance determining factors for jumping height in squat jumping individually. A measurement system similar to a leg press supplies the position, velocity and force data as function from time of several leg extension movements. A modified Hill type model uses this as input data. A data fitting algorithm determines the unknown muscle properties which are parameters of the model. This knowledge helps planning and controlling the training process. Furthermore it is possible to estimate performance development by simulation.